Identification of BMP15 Exon 2 for fecundity traits by PCR-RFLP and nucleotide sequencies in Kejobong goat - A. Febriana; S. Sutopo; E. Kurnianto (Diponegoro University, 2017)
Kejobong goat is known as prolific and high productivity goat breed in Indonesia. PCR-RFLP and sequencing technique was established in the present study to accomplish the polymorphisms of Bone Morphogenetic Protein 15 (BMP15) gene exon 2 on Kejobong goat does. The blood samples was collected from 48 Kejobong does which were selected based on their litter size. The size of PCR amplification of BMP15 gene exon 2 was 837 bp. The product of PCR-RFLP technique digested by HinfI enzyme showed that the samples were monomorphic. Authentication result using nucleotide sequencing found 4 substitution (A391G, C464G, T828C and C830G), 1 alignment gap (site 817) and 1 insertion nucleotide (site 822). This mutations caused 6 haplotypes formatted. The mutants of BMP15 exon 2 on Kejobong goats indicated that this breed had their own mutation controling the prolific trait. The phylogenetic tree build on the sequences of BMP15 gene exon 2 of Kejobong goats was grouped into 3 clusters. The alignment gap indicated to be the specific marker for the prolific trait (duplet) in Kejobong goat. The particular insertion site could be the recognition site of Kejobong goat based on BMP15 exon 2.